Bilateral variant origin of the inferior phrenic artery - Angel; Anjali Jain (Wolters Kluwer Medknow Publications, 2019)
The inferior phrenic arteries (IPA) arise from aorta, just above the level of celiac artery. Although descriptions of the right and left phrenic arteries are typically brief, the inferior phrenic arteries have received attention in recent years because of its involvement in treating unresectable hepatocellular carcinoma (HCC) by using transcatheter embolization. Since IPA contributes to the arterial supply of adrenal glands, they are important in angiographic examination of adrenal lesions. During routine dissection for MBBS students, bilateral variant origin of inferior phrenic arteries was observed. In this case, coeliac artery was tortuous and it measured 2 cm in length and 0.6 cm in diameter. The right IPA originated from the coeliac artery as a common trunk. This common trunk divided into two. One branch formed the right IPA and the other branch formed the superior suprarenal artery. On the left side, a common trunk originated from coeliac artery which divided into two branches. One branch joined the splenic artery and the other branch again formed a common trunk which further divided into two i.e superior suprarenal artery and left IPA. In patients with left suprarenal mass or oesophgo- gastric junction hemorrhage, certain interventional procedures such as selective IPA angiography is necessary. Due to variable anatomy of its origin, cannulation of IPA can be challenging. Therefore, the knowledge of this type of variations should be kept in mind by the surgeons and care should be taken to avoid unintentional sectioning of small caliber arteries.